Product and Labor Market Imperfections and Scale Economies: Micro-Evidence on France, Japan and the Netherlands - Sabien Dobbelaere; Kozo Kiyota; Jacques Mairesse (Tinbergen Institute, 2013)
Allowing for three labor market settings (perfect competition or right-to-manage bargaining, efficient bargaining and monopsony), this paper relies on an extension of Hall's econometric framework for estimating simultaneously price-cost margins and scale economies. Using an unbalanced panel of 17,653 firms over the period 1986-2001 in France, 8,725 firms over the period 1994-2006 in Japan and 7,828 firms over the period 1993-2008 in the Netherlands, we first apply two procedures to classify 30 comparable manufacturing industries in 6 distinct regimes that differ in terms of the type of competition prevailing in product and labor markets. For each of the three predominant regimes in each country, we then investigate industry differences in the estimated product and labor market imperfections and scale economies. We find important regime differences across the three countries and also observe differences in the levels of product and labor market imperfection s and scale economies within regimes.
Keywords: C23; D21; J50; L13; 330; Rent sharing; monopsony; price-cost mark-ups; production function; panel data; Skalenertrag; Unvollkommener Markt; Mark-up Pricing; Monopson; Industrie; Japan; Frankreich; Niederlande